Investigations on Amphoteric Chitosan/TiO2 Bionanocomposites for Application in Visible Light Induced Photocatalytic Degradation - M. Bahal; N. Kaur; Nidhi Sharotri; Dhiraj Sud (Advances in Polymer Technology)
The present investigation reports the greener synthesis and characterization of novel acrylic acid grafted amphoteric chitosan/TiO2 (CAT) bionanocomposites using ultrasonic radiations. This was done by grafting of acrylic acid onto chitosan in the presence of potassium persulfate by free radical polymerization reaction. The uniform distribution of metal oxide in CA/TiO2 nanocomposites was achieved on grafted acrylic acid/chitosan which contains a weak anionic group (-COOH) using ultrasonication technique. Physiochemical techniques such as X-ray diffraction (XRD), field emission scanning electron microscope (FE-SEM), Fourier Transform Infra-Red spectroscopy (FT-IR), Energy Dispersive X-ray spectroscopy (EDX), and Thermal Gravimetric Analysis (TGA) were employed to characterize synthesized CAT. Nanocomposite CAT was applied for degradation of industrial dye. Malachite green (MG) often presents in the waste waters. The degradation kinetics were studied by monitoring the photocatalytic reaction for degradation of MG under visible light, and the rate constant of the reaction was found to be 7.13x10−3min−1. The current research work opens vistas for the new dimensions in the area of water treatment by solving the issues related to degradation reaction efficiency in visible light and cost effectiveness.